KAPASITAS EKSPOR KOPI HS 090111 INDONESIA KE AMERIKA SERIKAT DIPENGARUHI OLEH BERBAGAI VARIABEL - Windian, Kiki; Darwanto, Dwidjono Hadi; Jamhari, Jamhari (Institute of Computer Science (IOCS), 2025)
Coffee commodities have a large contribution to the international market because coffee can be a raw material for various industries in the world market. Indonesia is an international coffee exporter and the world's main coffee importer is the United States. With the conditions of coffee exports and imports in the international market, various variables can affect the level of international trade. The purpose of this study is to understand the variables that can affect the volume of Indonesian coffee exports to the United States. The basis of the descriptive research method, data type and quantitative data origin and time series in secondary data for 45 years from 1975 to 2020, with the VECM analysis technique. This study shows that in the long term, Indonesian HS 090111 coffee is influenced by global tea prices, global sugar prices, global coffee prices, real exchange rates and US GDP. In the short term, the global coffee price of the previous two years can affect the capacity of Indonesian coffee exports to the United States. The volume of Indonesian coffee exports is influenced by several variables that cannot be controlled by Indonesia, so the government needs to increase coffee production.